Preparation and structural characterization of sodium polyphosphate coacervate as a precursor for optical materials - Franco, D. F. [UNESP]; Barud, H. S.; Santagneli, S. [UNESP]; Lamarca, R. S.; Santos, Bruno F. [UNESP]; Silva, M. A.P.; de Oliveira, L. F.C.; Ribeiro, S. J.L. [UNESP]; Nalin, M. [UNESP] (Elsevier, 2016)
This paper describes the preparation of Sodium Polyphosphates Coacervates (NaPC) through the direct addition of different methanol molar fractions to a sodium polyphosphate solution. The presence of methanol reduces the dielectric constant medium and it promotes the coacervate formation. Rheology measurement shows that the NaPC viscosity is dependent on a methanol molar fraction, which is caused by the dielectric constant reduction of the water-methanol mixture. Raman spectra for the lyophilized NaPC show that the symmetric P-Ot stretching mode is more sensitive than the symmetric P-Ob stretching mode, due to the approach of the adjacent polyphosphate chains. The 31P NMR spectra also confirm a decrease in the Q2/Q1 ratio because of the methanol content. Besides, we have obtained transparent soft Glass-Materials to melt NaPC at 800 °C.
Keywords: Coacervates; Glasses; Nuclear magnetic resonance (NMR); Optical properties